2005
DOI: 10.1503/cmaj.1041203
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular hyaluronic acid for the treatment of osteoarthritis of the knee: systematic review and meta-analysis

Abstract: Review SynthèseO steoarthritis affects about 10% of the population over 55 years of age. Of those, one-quarter are severely disabled.1 The condition is characterized by degeneration of the articular cartilage and subsequent subchondral bone changes. The underlying mechanisms remain unknown, but the glycosaminoglycan-proteoglycan matrix may play a major role. 2 Hyaluronic acid, a glycosaminoglycan, is widely used for the treatment of osteoarthritis of the knee. A survey of 2 general practices in the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
190
0
19

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(211 citation statements)
references
References 38 publications
2
190
0
19
Order By: Relevance
“…This result was comparable with HA injection into the knee with OA estimated by meta-analysis; for example, Wang et al reported that the RR of adverse events was 1.19 (95% CI 1.01, 1.41) (21). Arrich et al also reported an RR of adverse events of 1.08 (95% CI 1.01, 1.15) (42). Therefore, the adverse events mostly of minor clinical relevance reported in the various RCTs included in this meta-analysis seem to indicate that injection of HA is a safe technique for treatment of chronic painful shoulder.…”
Section: Discussionmentioning
confidence: 60%
“…This result was comparable with HA injection into the knee with OA estimated by meta-analysis; for example, Wang et al reported that the RR of adverse events was 1.19 (95% CI 1.01, 1.41) (21). Arrich et al also reported an RR of adverse events of 1.08 (95% CI 1.01, 1.15) (42). Therefore, the adverse events mostly of minor clinical relevance reported in the various RCTs included in this meta-analysis seem to indicate that injection of HA is a safe technique for treatment of chronic painful shoulder.…”
Section: Discussionmentioning
confidence: 60%
“…It is found the patients with arthritis have lower level of glucose and protein in synovial fluid which was considered as an important factor aggravating inflammation and damage of joint [12]. As a kind of hypertonic solution, it can increase osmotic pressure in joint cavity and relieve tissue edema.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively expensive viscosupplement [78] is available as naturally occurring hyaluronan and as synthetic hylan G-F 20. Compared to placebo, viscosupplements were shown in a Cochrane review to improve pain and function by approximately up to 54 and 32 % compared with baseline levels, respectively, in the 5-to 13-week postinjection period [79].…”
Section: Intraarticular Hyaluronic Acidmentioning
confidence: 99%